Effect of several parameters on non-autoclaved aerated concrete: use of recycling waste perlite. Issue 1 (2nd January 2022) - Fabien, Aurélie; Sebaibi, Nassim; Boutouil, Mohamed
Abstract: This article presents the results of an experimental study on a new protocol to create a non-autoclaved cellular concrete containing a partial substitution of sand by an equivalent volume of pure perlite and perlite waste. The development of the experimental protocol was performed based on a series of steps to control each parameter that influences this swelling procedure (temperature, water content, duration, containment, restricted swelling and filling height). Each parameter has been the subject of feasibility test, process and thermal validation analysis. The perlite pure or waste used for volume substitution (30%/30%) of sand was characterised by a lower density, which allowed the concrete to swell under non-autoclaved conditions. Each element were tested to evaluate their influence on thermal insulation properties. Presence of recycled product decreased the mechanical strength but promoted thermal insulation properties. An optimisation of the formulation is needed to keep a high porosity but obtained a better mechanical strength. With an increase of 2% of cement we can increase the mechanical strength value of 21%. Based on the investigated formulations, 100% expanded material with a thermal conductivity of 0.176 W/m.K was achieved. As such, the non-autoclaved swelling protocol facilitated the development of insulation material based on recycled products.